Bacterial cellulose-derived carbon nanofibers as both anode and cathode for hybrid sodium ion capacitor. Issue 13 (24th February 2020) - Xu, Jiaxin; Liu, Zhanying; Zhang, Fang; Tao, Jie; Shen, Laifa; Zhang, Xiaogang
Abstract : A hybrid sodium ion capacitor is constructed by the double carbon electrode, whose precursors are both from nanofibers of bacterial cellulose, showing a superior electrochemical capacitive performance. Abstract : Hybrid ion capacitors (HICs) based on insertion reactions have attracted considerable attention due to their energy density being much higher than that of the electrical double-layer capacitors (EDLCs). However, the development of hybrid ion capacitors with high energy density at high power density is a big challenge due to the mismatch of charge storage capacities and electrode kinetics between the battery-type anode and capacitor-type cathode. In this work, N and O dual doped carbon nanofibers (N, O-CNFs) were combined with carbon nanotubes (CNTs) to compose a complex carbon anode. N, O dual doping effectively tuned the functional group and surface activity of the CNFs while the integration of CNTs increased the extent of graphitization and electrical conductivity. The carbon cathode with high specific surface area and high capacity was obtained by the activation of CNFs (A-CNFs). Finally, a hybrid sodium ion capacitor was constructed by the double carbon electrode, which showed a superior electrochemical capacitive performance. The as-assembled HIC device delivers a maximum energy density of 59.2 W h kg −1 at a power density of 275 W kg −1, with a high energy density of 38.7 W h kg −1 at a power density of 5500 W kg −1 .